Women with Myocardial Infarction Present Subtle Cognitive Difficulties on a Neuropsychological Battery After Exposure to a Social Stressor - Poitras M; Narvaez Linares NF; Lambert M; Browndyke JN; Plamondon H (Psychology Research and Behavior Management, 2022)
Marilou Poitras,1,* Nicolás Francisco Narvaez Linares,1,* Maude Lambert,1 Jeffrey N Browndyke,2 Hélène Plamondon1 1Behavioural Neuroscience Group, School of Psychology, University of Ottawa, Ottawa, Ontario, Canada; 2Department of Psychiatry and Behavioural Medicine, Division of Behavioral Medicine & Neurosciences, Duke University Medical Centre, Durham, NC, USA*These authors contributed equally to this workCorrespondence: Hélène Plamondon, University of Ottawa, School of Psychology, Behavioural Neuroscience Group, 136 Jean-Jacques Lussier, Vanier Hall, Room 2082, Ottawa, Ontario, Canada, Email Helene.Plamondon@uottawa.caObjective: Myocardial infarction (MI) is the primary cause of mortality and morbidity in women, but its sequelae remain largely understudied. Given the heart–brain relationship, our study aimed to further understand stress’s impact on regulating cognitive function post-MI. Specifically, our study evaluated the effect of stress induced using the Trier Social Stress Test (TSST), on neuropsychological function in women who have or have not experienced MI.Methodology: To do so, women (mean age = 59.41 yrs) with (WHxMI = 13) or without () a history of MI were exposed to the TSST prior to completion of a series of standardized neuropsychological tests: the Montreal Cognitive Assessment (MoCA), Control Oral Word Association (COWA), Rey Complex Figure and Recognition (RCFT), Trail Making Test (TMT), and Auditory Consonant Triagrams (ACT).Results: Our findings support MI to be associated with impairments in working memory affecting immediate recall of ACT, as well as visuospatial impairments in the RCFT copy trial, marked by poorer drawing accuracy and incorrect placement of figure elements. Overall, WHxMI required more time to complete the neuropsychological assessment (WHxMI 166.57 ± 12, 155.00 ± 6.57; p < 0.01).Conclusion: Together, these findings support cognitive impairments noted following a social stressor to remain subtle in WHxMI. Our study highlights the need for the development of more sensitive tools to screen for neuropsychological impairments in women with MI and the importance of assessing performance in a variety of testing conditions.Keywords: heart attack, cognitive function, executive functions, visual memory, verbal fluency